Penerapan Sistem Manajemen Mutu ISO 9001:2008 Terhadap Peningkatan Kinerja Politeknik Negeri Lampung - Nurmala Nurmala (Jurnal Ilmiah ESAI, 2015)
Management Accounting states that the performance of an organization is not only seen on the financial performance but also in terms of non-financial. Non-financial performance assessment can be done by using a system of production and just-in-time distribution, employee empowerment, balance scorecard, reengineering, total quality control or quality management system known as ISO 9001: 2008.  Universities and colleges are required to be of good university governances. College performance typically uses non-financial ratings in the form of ISO 9001: 2008. State Polytechnics of Lampung is one of the colleges that has implemented quality management system ISO 9001: 2008. This study is to know the influence of the implementation of quality management system ISO 9001: 2008 to the improvement of performance of State Polytechnics of Lampung. This study assessed the performance of the employees.  The populations are the lecturers and academic staffs of  the department which has implemented the quality management system ISO 9001: 2008 as many as 160 people. Based on Solvin formula, the number of the sample is 58 people. The methods of data collection is the questionnaire containing indicators of the quality management system ISO 9001: 2008 and indicators of employee performance evaluation.  The data were analyzed through regression analysis. The results showed that the calculated F value of 85.671 with a significance level of 0.000. Because the Probability (0,000) is much smaller than 0.05, then the hypothesis is proven that the quality management system ISO 9001: 2008 has a significant influence on employee performance improvement in State Polytechnics of Lampung. Keywords: Management Accounting, performance, quality management system, and ISO 9001: 2008.